Analysis of Topological Structure of Series Mechanism with All Rotating Pair - Feiyang Lu; Xianshuang Zhu; Liangliang Zhang (Jixie chuandong)
Based on the topological structure theory of position and orientation characteristic （POC） set， a kind of series open chain mechanism composed of all rotating pairs is studied， and the POC set of vertical and parallel structures are compared. Methods using to analyze the structure are presented. Finally， the topological structure of 7R series mechanism is analyzed by using these methods.